Theory and Problems of trigonometry - Ayres Frank and Moyer Robert E. (Tata McGraw Hill Pub., New Delhi, 2005)
Stats/Maths
ENGLISH
Keywords: Theory and Problems of trigonometry; Stats/Maths; Stats/Maths